Chemical characterisation of Nigerian red propolis and its biological activity against Trypanosoma Brucei. Issue 2 (11th December 2015) - Omar, Ruwida M. K.; Igoli, John; Gray, Alexander I.; Ebiloma, Godwin Unekwuojo; Clements, Carol; Fearnley, James; Edrada Ebel, Ru Angeli; Zhang, Tong; De Koning, Harry P.; Watson, David G.
Abstract: Introduction: A previous study showed the unique character of Nigerian red propolis from Rivers State, Nigeria (RSN), with regards to chemical composition and activity against Trypanosoma brucei in comparison with other African propolis. Objective: To carry out fractionation and biological testing of Nigerian propolis in order to isolate compounds with anti‐trypanosomal activity. To compare the composition of the RSN propolis with the composition of Brazilian red propolis. Methodology: Profiling was carried out using HPLC‐UV‐ELSD and HPLC‐Orbitrap‐FTMS on extracts of two samples collected from RSN with data extraction using MZmine software. Isolation was carried out by normal phase and reversed phase MPLC. Elucidation of the compounds with a purity > 95% was performed by 1D/2D NMR HRMS and HRLC‐MS n . Results: Ten phenolic compounds were isolated or in the case of liquiritigenin partially purified. Data for nine of these correlated with literature reports of known compounds i.e. one isoflavanone, calycosin (1); two flavanones, liquiritigenin (2) and pinocembrin (5); an isoflavan, vestitol (3); a pterocarpan, medicarpin (4); two prenylflavanones, 8‐prenylnaringenin (7) and 6‐prenylnaringenin (8); and two geranyl flavonoids, propolin D (9) and macarangin (10). The tenth was elucidated as a previously undescribed dihydrobenzofuran (6). The isolated compounds were tested against Trypanosoma brucei and displayed moderate to high activity. Some of the compounds tested had similar activity against wild type T. brucei and two strains displaying pentamidine resistance. Conclusion: Nigerian propolis from RSN has some similarities with Brazilian red propolis. The propolis displayed anti‐trypanosomal activity at a potentially useful level. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The proton and carbon data for the nine known compounds isolated from Nigerian propolis are shown in S1. 1 H, 13 C, COSY, HMBC and HMQC NMR spectra for riverinol are shown in S2. S3 shows extracted ion traces for retusapurpurins. Table S4 summarises the exact masses and retention times for the top 200 compounds by intensity in Nigerian red propolis. S5 shows some examples of the plots used to determine EC50 values of compounds tested against T.brucei .